Assessment of the menstrual problems among teenage girls: A tertiary care center study - S Divya; Titty Mary Thomas; Rajunaik Ajmeera; Ambika Hegde; Taral Parikh; Shruti Shivakumar (Wolters Kluwer Medknow Publications, 2023)
Introduction: Due to shame over discussing menstruation and fear of illness, many adolescent girls with monthly problems never visit their family doctor or gynecologist. The presentation can be delayed as a result. The current study's goal was to assess the sociodemographic characteristics of adolescent females experiencing menstruation issues and the nature of those problems, and how they were handled. Materials and Methods: The problems faced by the adolescent girls attending the Department of Obstetrics and Gynecology were analyzed retrospectively, and all their study characteristics and conditions were evaluated. The descriptive demographics are only represented in the current study. Results: Two hundred-two teenage girls with menstruation issues visited our hospital overall. 64% of them were late adolescents, 96% lived in cities, 89 were unmarried, and 50% belonged to the middle class socioeconomically. Amenorrhea, dysmenorrhea, and irregular menstrual periods affected 86 (61%) people, 38 (27%) people, and 17 (12%) people, respectively. Patients were treated with appropriate counseling and medicinal and/or surgical care. Conclusion: Most of the teenage girls in our study had anemia. Therefore, it is essential to educate people on the importance of nutrition, different menstrual disorders, normal physiology, and the prevention and management of anemia. Adolescent-friendly health care has been attempted and partially developed in India's governmental and private systems. As a result, counseling and management of adolescent menstrual difficulties must be offered in the current health and medical care systems.